Fish diversity and heavy metal accumulation of Pb, Cu and Zn after Mount Sinabung Eruption in Benuken River, North Sumatra, Indonesia - Melda Agnes Pebriani Sinuraya; Ternala Alexander Barus; Syafruddin Ilyas (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pebriani MA, Barus TA, Ilyas S. 2021. Fish diversity and heavy metal accumulation of Pb, Cu and Zn after Mount Sinabung Eruption in Benuken River, North Sumatra, Indonesia. Biodiversitas 23: 187-194. The Benuken River is a river that has been affected by the volcanic ash eruption of Mount Sinabung, one of the active volcanoes in Indonesia. This study further examines the diversity of fish species and the analysis of their tissues with regard to the heavy metal content of each species in the Benuken River, Berastepu Village, Karo Regency after the eruption of Mount Sinabung using atomic absorption spectroscopy (AAS). The fish and water sampling were carried out in March 2019 with two sampling points using the electrofishing technique. Furthermore, four species were documented, including Spotted barb (Puntius binotatus), River loaches (Homaloptera nebulosa), Mahseer (Tor soro), and Striped snakehead (Channa striata). The diversity index of the fish community from two study sites ranged between 0.012<H' <0.023 or was categorized as very low in diversity. Meanwhile, the heavy metals concentrations of Cu, Pb and Zn in the water of Benuken River were below tolerance level based on the Governmental Regulations No. 82 year 2001. The average heavy metal concentrations in fish tissue were also safe for consumption based on the standard quality by FAO/WHO (2004) with 0.0049 ppm, 0.0056 ppm and 0.3852 ppm of Pb, Cu and Zn, respectively.